Neuroscience: Exploring the brain - Paradiso, Michael A.; Paradiso, Michael A.; Bear, Mark F.; Connors, Barry W. (Philadelphia, Wolters Kluwer, 2016)
This book brings together the major techniques used in the isolation or enrichment of individual populations of organelles and other subcellular structures from plants with the goal that, by being able to isolate subcellular structures, the research and understanding of various facets of compartmentalized function in plant cells can be advanced. Written for the highly successful Methods in Molecular Biology series, expert contributors provide chapters that contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.
Glossary 901-924p.; References 925-952p.; Index 953-975p.
Keywords: Behavior; Brain; Changing brain; Spinal cord; Motor systems